Analysis Of The Influence Between Service Quality And Promotion On Customer Loyalty Of PT. Pelni Passenger Ships - Kuncoro, Yahya (Institut Transportasi dan Logistik Trisakti, 2024)
PT. Pelayaran Nasional Indonesia (PELNI) is a State-Owned Enterprise in the shipping sector, which is the largest in Indonesia. The number of PELNI passengers in recent years has fluctuated due to competition from other transportation modes that offer better services. The aim of this research is to determine the relationship between service quality and promotion on the customer loyalty of PT. PELNI's passenger ships. The research object is passengers who use PT. PELNI's passenger ship services with a random sample of 105 respondents. The research results show that improving service quality and promotion individually will increase customer loyalty because they have a strong relationship, but not as much as when improving service quality and promotion together because they have a very strong relationship.